Conceptualising cosmopolitan values in internationalised higher education: a capabilities approach - Bridges, Stephanie (2015)
The increasingly internationalised nature of higher education has enhanced the potential for students to benefit from a more diverse student body, yet there are gaps between the rhetoric and ideals of internationalisation and the lived realities for both home and international students. This paper advances the idea that fostering cosmopolitan values might be an educational focus for internationalisation. In this study I construct an intercultural ‘capability set’ as means of operationalising cosmopolitan values within higher education, by drawing on Kwame Anthony Appiah’s conception of cosmopolitanism, on the ‘capability approach’ of Amartya Sen and on data from 44 interviews with undergraduate home and international pharmacy students. Findings illustrated the value of the capability approach a means of evaluating students’ intercultural capabilities and potential of the capability set to be used as a heuristic tool for informing thinking about the creation of academic environments which promote justice, student agency and capability development.